Download presentation

Presentation is loading. Please wait.

Published byGervase Johnson Modified over 6 years ago

1
Find the x-intercept To find the y-intercept, we must use 0 for x. Substitute x = 0 into 2x + 3y = 6 and solve for y: 2x + 3y = 6 2(0) + 3y = 6 0 + 3y = 6 3y = 6 y = y = 2 Therefore, the y-intercept is b = 2, (0,2). Substite x=0 Simplify Solve for y

2
Find the y-intercept To find the x-intercept, we must use 0 for y. Substitute y = 0 into 2x + 3y = 6 and solve for x. 2x + 3y = 6 2x + 3(0) = 6 2x + 0 = 6 2x = 6 x = x = 3 Therefore, the x-intercept is 3, (3,0). Substitute y=0 Simplify Solve for x

3
Graphing the Equation Now, graphing using the y-intercept, 2, and the x-intercept, 3. Connect the two intercepts with a line. Plot the x and y – intercepts and graph the line 2x + 3y = 6

4
Graphing the Equation

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google